Screening and functional analysis of the differential peptides from the placenta of patients with healthy pregnancy and preeclampsia using placental peptidome - Chen, Tingting; Zhang, Zhongxiao; Lu, Qin; Ma, Jun (Frontiers in Genetics, 2022)
Molecular peptides play an extensive range of functions in the human body. However, no previous study has performed placental peptidome profiling. In the present study, 3941 peptides from human placental tissues were identified using peptidomics. Compared to healthy pregnant women, there were 87 and 129 differentially expressed peptides (DEPs) in the mild and severe preeclampsia groups, respectively. In the mild PE group, 55 and 34 DEPs had high and low expressions, respectively. In comparison, in the severe PE group, 82 and 47 DEPs had high and low expressions, respectively. Functional analysis of the precursor proteins of DEPs by gene ontology suggested that they are primarily involved in focal adhesion, extracellular matrix-receptor interaction, tight junction, and extracellular matrix. Network analysis using ingenuity pathway analysis software showed that the precursor proteins of DEPs were primarily related to the transforming growth factor-β (TGF-β)/Smad signaling pathway. Further molecular docking experiments showed that the AASAKKKNKKGKTISL peptide (placenta-derived peptide, PDP) derived from the precursor protein IF4B could bind to TGF-β1. Therefore, our preliminary results suggest that the actions of PDP may be mediated through the TGF-β1/Smad signaling pathway. Our results demonstrate that the placental bioactive peptides may regulate the placental function during PE progression.